Gilgit-Baltistan: and its saga of unending human rights violations - Bansal, Alok (New Delhi : Pentagon Press, 2018)
This book enlightens the readers about the geo-strategically significant and resource rich area that legally and constitutionally belongs to India but is under Pakistani occupation .it gives some interesting and hithero unknown facts about the history,culture and polity of the region,which will engross a layman and a scholar alike.It also gives a detailed picture of the contemporary situation of the region,mired in gross human rights vilolation.Armed with this vital information,it will easier to combat vested interests and inimical forces that are hell bent on usurping this strategically important region.
English
Keywords: Political violence -- Pakistan -- Gilgit-Baltistān; Human rights -- Economic rights